Plasticity-Related Activity in the Hippocampus, Anterior Cingulate, Orbitofrontal, and Prefrontal Cortex Following a Repeated Treatment with D(2)/D(3) Agonist Quinpirole - Brozka, Hana (Biomolecules, 2021)
Quinpirole (QNP) sensitization is a well-established model of stereotypical checking relevant to obsessive-compulsive disorder. Previously, we found that QNP-treated rats display deficits in hippocampus-dependent tasks. The present study explores the expression of immediate early genes (IEG) during QNP-induced stereotypical checking in the hippocampus, anterior cingulate cortex (ACC), orbitofrontal cortex (OFC), and medial prefrontal cortex (mPFC). Adult male rats were injected with QNP (0.5 mg/mL/kg; n = 15) or saline (n = 14) daily for 10 days and exposed to an arena enriched with two objects. Visits to the objects and the corners of the arena were recorded. QNP-treated rats developed an idiosyncratic pattern of visits that persisted across experimental days. On day 11, rats were exposed to the arena twice for 5 min and sacrificed. The expression of IEGs Arc and Homer1a was determined using cellular compartment analysis of temporal activity by fluorescence in situ hybridization. IEG-positive nuclei were counted in the CA1 area of the hippocampus, ACC, OFC, and mPFC. We found significantly fewer IEG-positive nuclei in the CA1 in QNP-treated rats compared to controls. The overlap between IEG expressing neurons was comparable between the groups. We did not observe significant differences in IEG expression between QNP treated and control rats in ACC, OFC, and mPFC. In conclusion, treatment of rats with quinpirole decreases plasticity-related activity in the hippocampus during stereotypical checking.